The impact of the rotation on the surface brightness of early-type stars. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Challouf, M.; Nardetto, N.; de Souza, A. Domiciano; Mourard, D.; Aroui, H.; Stee, P.; Meilland, A.
Abstract: The surface brightness colors (SBC) relation is a very important tool to derive the distance of extragalactic eclipsing binaries. However, for early-type stars, this SBC relation is critically affected by the stellar environment (wind, circumstellar disk, etc...) and/or by the fast rotation. We calculated 6 models based on the code of Domiciano de Souza et al. (2012 ) considering different inclinations and rotational velocities. Using these results, we quantify for the first time the impact of the rotation on the SBC relation.